New insight on facet-dependent physicochemical properties of anatase TiO2 nanostructures for efficient photocatalysis. Issue 72 (15th July 2016) - Wang, Wei; Fang, Jiaojiao; Zhou, Yingjie; Zhang, Wenyan; Lu, Chunhua
Abstract : Crystal growth mechanisms and physicochemical properties associated with the photocatalytic activities have been systematically investigated. Abstract : Anatase TiO2, whose performance depends strongly on the exposed facets, is an efficient photocatalyst in utilizing solar energy for environmental purification. Herein, we report the synthesis of a series of TiO2 nanoparticles, with the {001} facet percentage adjusted in the range of ca. 0–100%. Comprehensive studies on the crystal structure evolution mechanisms and the corresponding influence on the physicochemical properties were conducted. Unlike previous results, we found that directly comparing the band gaps of TiO2 with different percentages of the {001} facet and the corresponding influence on the photocatalytic activity are infeasible. Experimental results indicate that 73% is the optimized {001} facet percentage for the most efficient photocatalysis. In addition to the traditional factors ( e.g. crystallinity, specific surface area), this structure is also very efficient at separating the photo-carriers and adsorbing surface OH groups, which is different from previous results wherein more surface adsorbed F − ions result in less surface OH groups. This study may provide new insight on investigating the crystal facet engineering technique for efficient photocatalysis.